Oxidative stress markers after a race in professional cyclists - Cordova, A.; Sureda, A.; Albina, M. L.; Linares, V.; Belles, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
The aim was to determine the levels and activities of the oxidative stress markers in erythrocytes, plasma, and urine after a flat cyclist stage. Eight voluntary male professional trained-cyclists participated in the study. Exercise significantly increased erythrocyte, leukocyte, platelet, and reticulocyte counts. The exercise induced significant increases in the erythrocyte activities of catalase (19.8%) and glutathione reductase (19.2%), while glutathione peroxidase activity decreased significantly (29.3%). Erythrocyte GSSG concentration was significantly increased after exercise (21.4%), whereas GSH was significantly diminished (20.4%). Erythrocyte malondialdehyde levels evidenced a significant decrease 3 h after finishing the stage (44.3%). Plasma malondialdehyde, GSH and GSSG levels significantly decreased after 3 hr recovery (26.8%, 48.6%, and 31.1%, respectively). The exercise significantly increased the F2-isoprostane concentration in urine from 359 ± 71 pg/mg creatinine to 686 ± 139 pg/mg creatinine. In conclusion, a flat cycling stage induced changes in oxidative stress markers in erythrocytes, plasma, and urine of professional cyclists. Urine F2-isoprostane is a more useful biomarker for assessing the effects of acute exercise than the traditional malondialdehyde measurement.